2016
DOI: 10.1093/jscr/rjw123
|View full text |Cite
|
Sign up to set email alerts
|

A case of postoperative recurrent cholangitis after pancreaticoduodenectomy successfully treated by tract conversion surgery

Abstract: A 69-year-old man, who had undergone pylorus-preserving pancreaticoduodenectomy (PD) (Imanaga procedure) for duodenum papilla cancer 13 years prior, had a history of repeated hospitalization due to cholangitis since the third year after surgery and liver abscess at the 10th year after surgery. Gastrointestinal series indicated no stenosis after the cholangiojejunostomy. However, reflux of contrast media into the bile duct and persistence of food residues were observed. We considered the cholangitis to be cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Some studies have suggested that a longer afferent loop or Roux-en-Y limb is a factor that prevents reflux and stasis in patients with biliary reconstruction [ 15 , 16 ], but there are also reports that shorter limb lengths are associated with fewer complications, so a certain view has not been reached [ 17 ]. In this case, the indication for surgery was also determined after careful consideration, referring to previous cases in which surgery was performed for nonobstructive retrograde cholangitis that developed after biliary reconstruction surgery [ 4 , 5 , 18 , 19 ]. The procedure was determined with reference to the Roux-en-Y extension to increase the distance between the route of oral intake and the bile duct jejunal anastomosis, among others [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that a longer afferent loop or Roux-en-Y limb is a factor that prevents reflux and stasis in patients with biliary reconstruction [ 15 , 16 ], but there are also reports that shorter limb lengths are associated with fewer complications, so a certain view has not been reached [ 17 ]. In this case, the indication for surgery was also determined after careful consideration, referring to previous cases in which surgery was performed for nonobstructive retrograde cholangitis that developed after biliary reconstruction surgery [ 4 , 5 , 18 , 19 ]. The procedure was determined with reference to the Roux-en-Y extension to increase the distance between the route of oral intake and the bile duct jejunal anastomosis, among others [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two clinical cases of this kind were presented by Japanese authors. In one case, it was necessary to convert the reconstructive scheme from the Imanagi to the Child method 13 years after the PD [18] with a good immediate result. In the second patient, recurrent reflux-cholangitis began to appear soon after PD.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 2016, Virgilio et al [9] found only 35 cases fulfilling the definition of merely post-surgical PLA [7,1011]. We add to them a number of cases – both in earlier [5,8,12–17] and later [18,19] publications. There are only two papers analyzing the problem of post-PD liver abscesses on large clinical material [10,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative benign biliary stenosis at the anastomotic site is one of the most common complications [ 6 8 ]. Reoperation or dilation of stenosis through the percutaneous transhepatic biliary drainage route has usually been performed, but these are invasive and negatively influence the quality of life.…”
Section: Discussionmentioning
confidence: 99%